2016
DOI: 10.1097/md.0000000000005257
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of infection and molecular characterization of blood-borne HIV, HCV, and HBV infections in HIV-1 infected inmates in Italy

Abstract: Coinfection of blood-borne hepatitis B and hepatitis C viruses (HBV and HCV, respectively) in human immunodeficiency virus type 1 (HIV-1)-positive individuals frequently occurs in inmate population and peculiar viral strains and patterns of virological markers may be observed.Plasma from 69 HIV-1-positive inmates was obtained from 7 clinical centers connected with correctional centers in different towns in Italy. HIV, HBV, and HCV markers were tested by commercial assays. Virus genotyping was carried out by se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 37 publications
3
22
1
1
Order By: Relevance
“…Of the 52 included studies, 48 were cross-sectional [ 6 , 7 , 9 , 19 31 , 33 , 35 59 , 61 – 66 ] and 4 were prospective cohort studies [ 10 , 32 , 34 , 60 ]. Of all, 50 studies reported HCV infection [ 6 , 7 , 9 , 10 , 19 63 , 65 ] and 23 studies reported either solely HBV infection or both HBV and HCV infections [ 19 , 21 , 25 , 28 , 32 , 34 37 , 41 , 43 – 46 , 52 , 54 56 , 58 , 60 , 64 – 66 ]. Regarding the study location, 21 studies were conducted in Europe [ 9 , 10 , 21 , 24 , 25 , 27 , 33 , 34 , 39 , 42 , 45 – 47 , 49 , 52 , 55 , 56 , 58 , 60 , 63 , 65 ], 18 were conducted in America [ 6 , 7 , 20 , 22 , 23 , 26 , 29 32 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 52 included studies, 48 were cross-sectional [ 6 , 7 , 9 , 19 31 , 33 , 35 59 , 61 – 66 ] and 4 were prospective cohort studies [ 10 , 32 , 34 , 60 ]. Of all, 50 studies reported HCV infection [ 6 , 7 , 9 , 10 , 19 63 , 65 ] and 23 studies reported either solely HBV infection or both HBV and HCV infections [ 19 , 21 , 25 , 28 , 32 , 34 37 , 41 , 43 – 46 , 52 , 54 56 , 58 , 60 , 64 – 66 ]. Regarding the study location, 21 studies were conducted in Europe [ 9 , 10 , 21 , 24 , 25 , 27 , 33 , 34 , 39 , 42 , 45 – 47 , 49 , 52 , 55 , 56 , 58 , 60 , 63 , 65 ], 18 were conducted in America [ 6 , 7 , 20 , 22 , 23 , 26 , 29 32 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of all, 50 studies reported HCV infection [ 6 , 7 , 9 , 10 , 19 63 , 65 ] and 23 studies reported either solely HBV infection or both HBV and HCV infections [ 19 , 21 , 25 , 28 , 32 , 34 37 , 41 , 43 – 46 , 52 , 54 56 , 58 , 60 , 64 – 66 ]. Regarding the study location, 21 studies were conducted in Europe [ 9 , 10 , 21 , 24 , 25 , 27 , 33 , 34 , 39 , 42 , 45 – 47 , 49 , 52 , 55 , 56 , 58 , 60 , 63 , 65 ], 18 were conducted in America [ 6 , 7 , 20 , 22 , 23 , 26 , 29 32 , 37 , 38 , 50 , 57 , 59 , 61 , 62 , 66 ], 2 in South-East Asia [ 41 , 48 ], 7 in East Mediterranean [ 28 , 36 , 40 , 43 , 44 , <...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we retrospectively examined HIV-infected patients and found that about 64.0% of them had been infected with HBV, which was lower than the rate reported from Italy showing that 81.2% of HIV-positive inmates had current or past HBV infection. [ 15 ] Most of these patients were seropositive only for HBcAb and seronegative for HBsAg, indicating that these patients were previously infected with HBV and had cleared HBsAg, indicating their “functional cure.” The number of patients who presented HBsAg-seropositive at least once in their clinical courses was 57, 7.9% among patients examined for HBV-related laboratory tests. This rate was a little bit higher than that reported by Phinius et al [ 16 ] showing 27 (6.2%) among 435 HIV-infected patients in Botswana experienced HBsAg-seropositive during 4-year period, possibly due to the difference in the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the incidence and mortality of liver diseases were rapidly increasing and the number of deaths caused by liver diseases were presented in the top 2 among all types of cancers in 2014 (Wang et al, ; Zhai et al, ). Most cases of liver diseases naturally originate from hepatitis, which is well known as a dynamic disease, commonly associated with infection/inflammation or cellular toxicity/injury factors, such as HBV and HCV (Sanarico et al, ). As the inflammation progresses, the conditions get worse and then probably develop into liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%